Analysis of the rs2476601 polymorphism of PTPN22 in Mexican mestizo patients with leprosy - Escamilla-Tilch, Mónica; Pérez-Suárez, Thalía Gabriela; Torres-Carrillo, Nora Magdalena; Rodríguez-Guillén, Rosario; Arenas-Guzmán, Roberto; Torres-Hernández, Marcela; Fafutis-Morris, Mary; Estrada-Parra, Sergio; Estrada-Garía, Iris; García-Lechuga, Maricela; Granados, Julio; Ramos-Payan, Rosalio (Biomedical reports, 2019)
Leprosy, a human chronic granulomatous disease caused by Mycobacterium leprae (M. leprae), remains endemic in certain countries despite the use of multidrug therapy. Recently, several host genes modulating the immune responses to M. leprae infection have been suggested to influence the acquisition and clinical course of leprosy. Lymphoid protein tyrosine phosphatase, encoded by the protein tyrosine phosphatase non-receptor type 22 (PTPN22) gene, serves a negative regulatory role in T cell activation. The non-synonymous single-nucleotide polymorphism (SNP) rs2476601 (1858C>T) has been associated with autoimmune diseases. Here, the present study investigated if rs2476601 polymorphism was associated with leprosy in a Mexican mestizo population. Genotyping was performed in patients with leprosy (n=189) and control subjects (n=231) from regions with higher incidence of leprosy. Genotypic (P=0.44) and allelic frequencies (P=0.45) of the rs2476601 polymorphism were similar between patients and controls; genotypic frequencies were 91 vs. 94% for CC and 9 vs. 6% for CT, and the TT genotype was absent in both groups. Allelic frequencies were 96 vs. 97% for C, and 4 vs. 3% for T. In the same way, the genotypic (P=0.46) and allelic frequencies (P=0.47) from MB patients and controls were similar. In conclusion, there was a lack of association of the PTPN22 rs2476601 polymorphism with the development of leprosy, which suggests that this SNP was not a genetic risk factor for leprosy in the Mexican mestizo population studied.